Tradisi Kalosara: Simbol Resolusi Konflik, Pendidikan Karakter, dan Konstruksi Sosial dalam Masyarakat Tolaki - Hardin, Hardin; Hadirman, Hadirman (Lembaga Yasin AlSys, 2025)
Kalosara is a traditional symbol that plays an important role in the lives of the Tolaki people. More than just a cultural heritage, Kalosara is a guideline for resolving conflicts, instilling character values, and forming a social order. Amid the rapid flow of modernization, this tradition remains a reference in maintaining social harmony and strengthening the collective identity of the Tolaki people. This study aims to understand how Kalosara functions in three main aspects, namely as a means of conflict resolution, a means of character education, and an element that forms the social structure of society. With this approach, this study wants to see how Kalosara remains relevant and upheld in everyday life. This research uses a library method. The library method as a writing mechanism relies on the enrichment of literature data sourced from: books, journals, and library documents that discuss Kalosara. The data collected is grouped thematically to find aspects of symbols of conflict resolution, character education, and social construction behind the meaning of the Kalosara tradition. The research findings indicate that Kalosara is an effective medium for conflict resolution for the Tolaki people. In addition, the values ​​contained in this tradition become a means of character education that aligns with the attitude of tolerance, togetherness, and respect for social norms. Kalosara also plays a role as a social glue that strengthens the cultural identity of the Tolaki community. The literature search provides a picture that the Kalosara tradition contains noble values ​​that can continue to be transmitted to future generations.